DFT Study of Complexation Reactions Involving Dicarboxylic Acids: Hydrogen Bonds, Influence of Solvent Nature - Kurmanova, A.F.; Abilkanova, F.Zh.; Rakhimzhanova, A.S.; Pustolaikina, I.A. (KU Publ., 2022)
Quantum chemical studies of the protolytic ability of some dicarboxylic acids are carried out. The geometric and kinetic parameters of the dimeric molecules of maleic, succinic, tartaric, oxalic, and adipic acids are investigated. The dimerization energies of these substances are determined by considering the basis set superposition error (BSSE). The effect of the presence of a carbon skeleton, unsaturated bonds, and hydroxy substituents on the dicarboxylic acids kinetic parameters is confirmed. The frontier molecular orbitals of the studied dimeric acids molecules are considered and the HOMO-LUMO energy gap is determined. The obtained values of the energy gaps show an increase in the stability of a number of cyclic compounds formed by the participation of two hydrogen bonds. The ability of the acids to form complexes with the 3,6-di-tert-butyl- 2-hydroxyphenoxyl semiquinone radical is studied. The effect of the nature of the solvent on the activation barrier of the complexation reaction of the semiquinone radical — dicarboxylic acid system is analyzed using the CPCM and IEFPCM models. The dependence of the energy parameter on the solvent polarity is established using the examples of toluene, tetrahydrofuran, and nitrobenzene. The DFT method at the B3LYP level, together with the 6-31+G (d, p) basis set, is used to optimize molecular structures. The calculations are carried out using the Gaussian 16 Revision A.03 WIN64.
Дикарбон қышқылдары қатысатын комплекс түзілу реакцияларын DFT зерттеу: сутектік байланыс, еріткіш табиғатының әсері
ДФТ изучение реакций комплексообразования с участием дикарбоновых кислот: водородные связи, влияние природы растворителя
Keywords: quantum chemical calculations; density functional theory; hydrogen bond; intermolecular hydrogen bonds; transient formation; complex compounds; frontier molecular orbitals; dimerization energy; complexation energy; effect of the nature of the solvent